Tectonic Implications for the Gamburtsev Subglacial Mountains, East Antarctica, from Airborne Gravity and Magnetic Data - Guochao Wu; Fausto Ferraccioli; Wenna Zhou; Yuan Yuan; Jinyao Gao; Gang Tian (Remote Sensing, 2023)
The Gamburtsev Subglacial Mountains (GSMs) in the interior East Antarctic Craton are entirely buried under the massive East Antarctic ice sheet, with a ~50–60 km thick crust and ~200 km thick lithosphere, but little is known of the crustal structure and uplift mechanism. Here, we use airborne gravity and aeromagnetic anomalies for characteristic analysis and inverse calculations. The gravity and magnetic images show three distinct geophysical domains. Based on the gravity anomalies, a dense lower crustal root is modelled to underlie the GSMs, which may have formed by underplating during the continental collision of Antarctica and India. The high frequency linear magnetic characteristics parallel to the suture zone suggest that the upper crustal architecture is dominated by thrusts, consisting of a large transpressional fault system with a trailing contractional imbricate fan. A 2D model along the seismic profile is created to investigate the crustal architecture of the GSMs with the aid of depth to magnetic source estimates. Combined with the calculated crustal geometry and physical properties and the geological background of East Antarctica, a new evolutionary model is proposed, suggesting that the GSMs are underlain by part of a Pan-African age advancing accretionary orogen superimposed on Precambrian basement.